PENGELOLAAN RESIKO ANGGARAN TERHADAP KINERJA ORGANISASI PADA PT SUMITOMO INDONESIA - Bintang Narpati; Indra Lubis; Endah Prawesti Ningrum (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2020)
The purpose of this study is to measure the level of budget risk management on organizational performance at PT. Sumitomo Indonesia. The method used is quantitative descriptive analysis with a purposive method of 35 (three five-five) respondents. Using a simple linear regression analysis technique with a hypothesis: Is there a significant influence between budget risk management on organizational performance at PT. Sumitomo Indonesia The results of the study indicate that there is a significant influence between budget risk management and organizational performance by 50%. If budget risk management is carried out according to procedures and does not experience leakage or any discrepancy in the budget, it will significantly improve organizational performance. The organization will not suffer losses, but the improvement in organizational performance is not only influenced by the management of budget risk, but there are several other factors that influence it, such as budgetary oversight, financial statement management and which support in improving organizational performance. Keywords: budget risk management and organizational performance